Excimer laser-produced biodegradable photopolymer scaffolds do not induce immune rejection in vivo - Farkas Balázs; Zsedényi Ádám; Sebestyén Edina; Romano Ilaria; Nagy Katalin; Diaspro Alberto; Brandi Fernando; Buzás Krisztina; Beke Szabolcs (2015)
Following our previous works of in-vitro tests, the biocompatibility of photopolymer scaffolds was tested against immune responses in vivo. Neither relevant immune reactions nor the rejection of implanted scaffolds was detected, being an essential step for in vivo implantation of excimer laser-prepared scaffolds. The scaffolds were fabricated by UV excimer laser photocuring at 308 nm. Af-ter two weeks of transplantation neither inflammatory response nor reactive immune activation was detected based on the chemokine and cytokine profile. As a sign of biodegradability of the scaffolds, we detected macrophage infiltration and phagocytosis of the biopolymer at the site of implantation. Our results suggest that poly(propylene fumarate) (PPF): diethyl fumarate (DEF) (7: 3 w/w) scaf-folds have appropriate properties for in vivo applications.